Physiotherapists' assessment and management of psychosocial factors (Yellow and Blue Flags) in individuals with back pain. (October 2013) - Gray, Heather; Howe, Tracey
Abstract : Background: Personal and work-related psychosocial factors play an important role in persisting symptoms and delaying return to work in individuals with back pain. Therefore, it is essential that physiotherapists have the motivation and skills to assess and manage psychosocial factors as part of back pain management. Objectives: To systematically review and summarize the literature on physiotherapists' perceptions of and skills in assessing and managing psychosocial factors (Yellow and Blue Flags) in individuals with back pain. Methods: Searches were conducted of the: Ovid versions of MEDLINE, PsycINFO and EMBASE; EBSCO CINAHL; Cochrane Database of Systematic Reviews; Cochrane Central Register of Controlled Trials (Clinical Trials); and Physiotherapy Evidence Database (PEDro) from inception until end October 2011. Results: There were 384 hits of which 17 papers describing 15 studies met the inclusion criteria; these were: two randomized controlled trials; two observational studies; six survey based studies; two qualitative studies; and three using Delphi consensus development. Studies found that although physiotherapists theoretically support a biospychosocial management approach to back pain, in practice few are doing so adequately, even following training in cognitive behavioral principles. Physiotherapists expressed reluctance to engage in the management of work-related psychosocial factors (Blue Flags), perceiving that tackling work issues was outside their professional role. Conclusions: Despite evidence of the barriers to doing so, we put out a call to action that physiotherapists embrace the importance of integrating psychosocial factors in their everyday professional practice. In particular, gaining confidence in tackling Blue Flags is critical to establish physiotherapists as essential players in combating the growing public health concern of worklessness.